2016
DOI: 10.1177/0194599815626126
|View full text |Cite
|
Sign up to set email alerts
|

Does Type of Pharyngeal Packing during Sinonasal Surgery Have an Effect on PONV and Throat Pain?

Abstract: Despite commonly used practices, usage of different types of pharyngeal packing did not affect incidence of PONV and throat pain, nor did usage of no packing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 10 publications
0
46
0
Order By: Relevance
“…The outcomes at the early (immediate postoperative recovery state) and middle (2 hours postoperative) stages showed reciprocal patterns; however, the total amount of administered antiemetics within 24 hours postoperative was statistically similar between the two groups. Although ingested blood is a very potent emetic, PONV is multifactorial, involving elements such as individual patient factors, intraoperative management, and postoperative care . Thus, the use of pharyngeal packs in nasal surgery theoretically could prevent the ingestion of blood, thereby reducing PONV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The outcomes at the early (immediate postoperative recovery state) and middle (2 hours postoperative) stages showed reciprocal patterns; however, the total amount of administered antiemetics within 24 hours postoperative was statistically similar between the two groups. Although ingested blood is a very potent emetic, PONV is multifactorial, involving elements such as individual patient factors, intraoperative management, and postoperative care . Thus, the use of pharyngeal packs in nasal surgery theoretically could prevent the ingestion of blood, thereby reducing PONV.…”
Section: Discussionmentioning
confidence: 99%
“…The side effects and complications of oropharyngeal packing are primarily throat pain and mucosal injury. The primary outcome for this meta‐analysis was the incidence of moderate‐to‐severe PONV during the first postoperative day after nasal surgery under general anesthesia . Outcomes associated with pharyngeal packing during nasal surgery were compared against a control (no packing).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it would be necessary to evaluate the favorable effect or adverse effect of tranexamic acid in nasal surgery. Additionally, the incidence of postoperative nausea and vomiting (PONV) after nasal surgery has been reported to be 34% to 65% in various studies, which would be higher than 20% to 30% of incidence of PONV in all surgical patients after general anesthesia . In particular, because the nose and paranasal sinuses are highly vascularized structures, operations involving these regions may cause significant bleeding .…”
Section: Introductionmentioning
confidence: 99%
“…It concluded that further adequately powered trials are needed to confirm the effect of pharyngeal packing on throat pain and PONV . Following this review, three randomised controlled trials with relatively large number of patients showed that hypopharyngeal packs have no effect on throat pain and PONV . This contradicts the results of Erkalp et al, who reported that hypopharyngeal packs can result in significantly increased incidence of aphthous stomatitis and throat pain in the first 3 days following nasal surgery.…”
Section: Discussionmentioning
confidence: 86%
“…Basha et al and Karbasforushan et al compared the use of hypopharyngeal pack with no pack, and they found that hypopharyngeal packing is associated with a significantly increased incidence of postoperative throat pain. Contradictorily, other studies concluded that pharyngeal packs have no effect on postoperative throat pain …”
Section: Introductionmentioning
confidence: 99%